Prenatal screening for congenital malformations: diagnosis and management in low and medium income countries - Ipyana H. Mwampagatwa; James Charles (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2016)
Prenatal screening for foetal malformation is an important component of prenatal care. Unfortunately, it has not been adequately addressed in many low and medium income countries (LMIC). The literature indicates that this condition is one of the most important causes of newborn deaths. There are many screening methods but most are expensive and some require intensive training. A relatively cheap, safe and easy-to-perform method of ultrasound can help identify more than 50% of foetal malformations. Unfortunately, this technique is not readily available and even when a diagnosis is made the option of pregnancy termination involves cultural and ethical issues. This case series attempts to address the challenges faced by LMIC care providers and clients.